The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1046/j.1365-3059.1998.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative epidemiology of Banana Bunchy Top Virus Disease and its control

Abstract: Models of a banana bunchy top virus disease epidemic were developed to incorporate the two key features of an epidemic in a plantation in the Philippines: an exponential increase in disease incidence over 10 years, and a declining gradient of incidence from the outside edge of the plantation to the centre. A non-spatial model consisted of three difference equations to describe the numbers of latently infected and of infectious plants in the plantation and the size of the inoculum source outside the plantation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…(Dale and Harding 1998). An intensive banana plant rogueing regime in the Philippines has been shown to effectively reduce secondary spread of BBTV (Smith et al 1998). Even greater success may be possible with kava dieback because the kava-CMV interaction appears to be similar to that of cassava and African cassava mosaic virus (ACMV).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Dale and Harding 1998). An intensive banana plant rogueing regime in the Philippines has been shown to effectively reduce secondary spread of BBTV (Smith et al 1998). Even greater success may be possible with kava dieback because the kava-CMV interaction appears to be similar to that of cassava and African cassava mosaic virus (ACMV).…”
Section: Discussionmentioning
confidence: 99%
“…Examples include the somewhat similar ACMVcassava pathosystem; when inoculum pressure was high and when much secondary spread occurred, stringent rogueing programmes failed (Thresh et al 1998). Smith et al (1998) concluded that in the presence of numerous external BBTV inoculum sources, rogueing was not effective for banana bunchy top control. In the case of kava and CMV, advantage can be taken of the non-persistent nature of the virus and this can be combined with natural benefits of traditional Pacific Island farming systems to combat these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Similar pest and disease surveys are operated in Malaysia and India, but seldom elsewhere. However, there are routine scouting operations to monitor the incidence and distribution of pests and diseases in large commercial enterprises growing banana and other export crops (Thresh, 1988;Smith et al 1998). The information is required to determine the need for control measures and to influence cropping practices and planting policy, but much of the information obtained is not readily available.…”
Section: Surveys Of Disease Incidence and Severitymentioning
confidence: 99%
“…These streaks consist of a series of ''dots'' and short lines ''dashes'' often known as ''Morse code'' streaking. If fruit is produced, hands may have distorted and twisted forms [41,51,43,12,14,32,42,39].…”
Section: Introductionmentioning
confidence: 99%
“…It is transmitted by arthropods, insects of the order Hemiptera, family Aphididae; Pentalonia nigronervosa in a persistent manner [26]. The virus spreads in Africa Burundi, Gabon and Egypt [14] and occurs in Australia, Pacific Islands, the Philippines, and Taiwan [12,36,31,42,17].…”
Section: Introductionmentioning
confidence: 99%